RETRACTED: The Influence of Profitability and Leverage on Tax Avoidance with Company Size as a Moderation Variable - Icah Putri Utama; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the effect of Profitability and Leverage on Tax Avoidance with Company Size as a Moderating Variable (Empirical Study of Manufacturing Companies in the Various Industries Sector Listed on the Indonesia Stock Exchange for the 2017-2021 period). The data source for this research uses secondary data in the form of financial reports published on the Indonesia Stock Exchange. In taking the sample for this study using a purposive sampling method and the samples used in this study were 12 companies. The data analysis technique used is hypothesis testing which is processed using the WarpPLS 7.0 application. Based on the results of this study it was found that Profitability has a significant negative effect on Tax Avoidance, Leverage has no effect on Tax Avoidance, Company Size does not moderate the effect of Profitability on Tax Avoidance, and Company Size does not moderate the influence of Leverage on Tax Avoidance.